2021
DOI: 10.1002/pep2.24246
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides provide wider coverage for targeting drug‐resistant bacterial pathogens

Abstract: We need new treatment options to control bacterial infections. Bacteria use several strategies to resist drug treatment, including modification of the drug target, and adaptation to a different lifestyle, such as intracellular niches within host cells. Drugs that act on diverse targets are less likely to induce resistance in bacteria, than current antibiotics acting on a single molecular target. Antimicrobial peptides have been explored as a new class of antibiotics because they selectively kill bacteria via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 196 publications
(379 reference statements)
0
6
0
Order By: Relevance
“…[ 42 ] It has been suggested that accumulation of AMPs in the bacterial membrane causes increased permeability due to the loss of membrane integrity (e.g., destabilization of the LPS layer). [ 43 ] With peptoid 29 , the mechanism leading to the internalization of the compound at low concentrations is not fully understood. However, the observed inhibition of bacterial metabolism and the increased intracellular RI values with fluorescent images proves peptoid internalization in the absence of visible pore formation at low peptoid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] It has been suggested that accumulation of AMPs in the bacterial membrane causes increased permeability due to the loss of membrane integrity (e.g., destabilization of the LPS layer). [ 43 ] With peptoid 29 , the mechanism leading to the internalization of the compound at low concentrations is not fully understood. However, the observed inhibition of bacterial metabolism and the increased intracellular RI values with fluorescent images proves peptoid internalization in the absence of visible pore formation at low peptoid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Here we describe the rational optimization of the selective, membrane-active PDIP scaffold. We identified an antiplasmodial potency-enhancing substitution (E16K) and incorporated this into a stable and selective scaffold (24) to produce a backbone cyclic PDIP analogue (26) with low micromolar activity against in vitro P. falciparum parasites (see Figure 7). The outcomes of this study represent a practical advance in developing the PDIP scaffold as an antimalarial molecule and provide a framework for monitoring and selecting desirable properties during peptide-based drug development.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Their toxicity and stability in vivo are two drawbacks that restrict their use [124]. Another drawback is their inherent limitations as peptides, such as stability, cytotoxicity, and bioavailability [125]. Natural AMPs are only useful for topical applications due to their pharmacological characteristics [126].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%